The application of high-density polyethylene floating docks to improve the connectivity of small islands - Muhammad Bilal Aditya; Januar Saleh Kaimuddin; Andi Muhammad Farhan; Nur Inna (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: A pier is an essential infrastructure in maritime transportation and inter-island connectivity. However, conventional piers are often less flexible, environmentally harmful, costly, and require regular maintenance, making them inefficient for remote islands. As an alternative, HDPE floating docks offer advantages in cost, installation speed, durability, and ease of maintenance. Southeast Sulawesi has around 651 islands, 86 of which are inhabited and have great potential in the fisheries and tourism sectors. Unfortunately, many piers in this region are unusable due to budget limitations and difficult construction access. HDPE floating docks can serve as a solution and even be utilized as platforms for water sports and recreation, supporting tourism development. Despite their potential, the application of floating docks remains limited. This study aims to design a floating dock made of HDPE as an alternative pier for islands with limited access. Methods: The design approach is based on technical analysis of local water conditions, including bathymetry, wave characteristics, and vessel activity loads. Findings: The HDPE structure has proven to be superior to concrete piers, mainly due to its modular and flexible form that allows for easy expansion. This makes HDPE floating docks an effective and practical solution for improving accessibility in remote island regions. Conclusion: This study finds that HDPE floating docks are a cost-effective, durable, and adaptable solution for improving inter-island connectivity. The Liwungan Island case demonstrates their technical feasibility and positive impacts on fisheries and tourism. Aligned with Blue Economy and Smart City initiatives, HDPE floating docks offer a scalable and sustainable alternative for small island maritime infrastructure. Novelty/Originality of this article: This article presents a site-specific HDPE floating dock design tailored to the hydro-oceanographic conditions and accessibility constraints of remote islands, integrating technical feasibility with fisheries and tourism functions as a scalable alternative to conventional piers.